2017
DOI: 10.1590/s1517-707620170001.0122
|View full text |Cite
|
Sign up to set email alerts
|

Pre-alvejamento de materiais têxteis com ozônio e avaliação de suas propriedades de superfície, físicas e tintoriais

Abstract: A inovação dos processos de beneficiamento de materiais têxteis é cada vez mais importante para possibilitar a redução no consumo de água e nos tempos de processo na indústria têxtil. O consumo de fibras têxteis no Brasil em 2014 foi de 13,3 kg por habitante, e para beneficiar estes tecidos são utilizados em média 80 litros de água para cada quilograma de substrato tratado. Este estudo visou aprimorar o processo de pré-alvejamento para tecidos têxteis utilizando o ozônio com o objetivo de reduzir o consumo de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Sample expose to ozone exhibits greater absorption as the oxidation induced by the ozone treatment appears to cause changes in both the surface and the internal structure of the polymer [32]. According to Burkinshaw [31], polyester has a low water adsorption due to the hydrophobicity of its surface groups, hence ozone treatment, which produces carboxyl and hydroxyl groups, may impart greater hydrophilicity [20]. We also observed that after a prolonged exposure of the fabric to ozone, a loss of absorption occurs.…”
Section: Evaluation Of Surface Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample expose to ozone exhibits greater absorption as the oxidation induced by the ozone treatment appears to cause changes in both the surface and the internal structure of the polymer [32]. According to Burkinshaw [31], polyester has a low water adsorption due to the hydrophobicity of its surface groups, hence ozone treatment, which produces carboxyl and hydroxyl groups, may impart greater hydrophilicity [20]. We also observed that after a prolonged exposure of the fabric to ozone, a loss of absorption occurs.…”
Section: Evaluation Of Surface Modificationmentioning
confidence: 99%
“…According to Wakida et al [18], ozone treatments alter both, the fiber's surface and its internal structure [19]. Several authors [10,17,20] have also found that ozone treatment has the potential of lower energy consumption during the processing of polyester fibers.…”
Section: Introductionmentioning
confidence: 99%